Analysis of Ambidexterity Leadership in Promoting Policy Networks for Marketing Innovation - Herdesviana, Dean; Farabi, Ahmad; Maswanto, Maswanto (CV. Civiliza Publishing, 2025)
This study investigates the role of ambidextrous leadership in driving marketing innovation through the strategic building and leveraging of policy networks. In an era of rapid market change, organizations face the critical challenge of balancing the exploration of new opportunities with the exploitation of existing advantages. Using a qualitative multiple case study approach, data was collected through in-depth interviews with senior marketing executives and innovation managers, participatory observations, and document analysis. The data was processed using NVivo 12 software, revealing distinct thematic patterns. The findings demonstrate that leaders who successfully employ ambidextrous behaviors proactively exploring new network connections (31% frequency) while efficiently exploiting existing relationships (28% frequency) significantly enhance their organization’s marketing innovation capabilities. These leaders act as pivotal architects of external networks, translating policy insights into competitive marketing strategies. However, the implementation faces challenges, including cross-sector collaboration barriers (11%) and resource allocation tensions (8%). Sentiment analysis further reflects these complexities, showing predominantly positive perceptions (67 documents) tied to strategic adaptability, alongside concerns about bureaucratic complexity (28 documents). The study contributes theoretically by extending ambidextrous leadership theory into the external domain of policy network management. Practically, it offers managers a framework for developing leadership capabilities that navigate dual imperatives, while providing policymakers insights into designing more effective innovation ecosystems. Ultimately, the research confirms that ambidextrous leadership is a vital dynamic capability for transforming policy network engagement into sustained marketing innovation.